Identity, social groups and communication - Elirea Bornman (Communicare)
The recent flourishing in discourses on identity in the social sciences as well as the fact that struggles of identity have become the paradigmatic form of social and political conflict in the modern world form the contextual framework of this article. Firstly, it explores the development of theorising and research on identity in a sister discipline of Communication Science, namely Psychology, and specifically the development of social identity theory that acknowledges the vital role of social groups in identity processes. Furthermore, it explores how some subdisciplines of Communication Science deal with identity issues and, more specifically, with the role of social identities in communicationrelated phenomena. An alternative theoretical framework for the study of communication and identity is discussed. Finally, attention is given to the way in which processes associated with identity could influence communication-related phenomena and could be incorporated in the theorising and research within various subdisciplines of Communication Science.